DAMPAK PERTUMBUHAN NILAI TUKAR RIIL TERHADAP PERTUMBUHAN NERACA PERDAGANGAN INDONESIA (SUATU APLIKASI MODEL VECTOR AUTOREGRESSIVE, VAR) - Zuhroh, Idah; Kaluge, David (Journal of Indonesian Applied Economics, 2007)
This study aimed to test the impact of the growth of real exchange rate towards thegrowth of  Indonesian trade balance by using Vector Autoregressive  (VAR) Model.By  using quarterly data  from 1983.1  to 2005.4 periods,  the  result obtained  is  inaccordance with  other  countries which  response  positively  the  depreciation  ofexchange rate in long term or follow the phenomenon of J-curve. However, the rate ofgrowth is still weak in explaining the growth of trade balance because the model isonly significant estimates at á and based on the decomposition of variation of growthsurprises of real exchange rate is only 2.7% in average which explained the variationof trade balance growth.Keywords: Jcurve, real exchange rate, trade balance Vector Autoregressive.